Indian Journal of Biotechnology: A Bibliometric Study - VELMURUGAN C; RADHAKRISHNAN N (Innovare Journal of Sciences, 2016)
This paper presents a bibliometric features and characteristics of the journal titled â€˜Indian Journal of biotechnology'. It publishes four issues per year by NISCAIR, New Delhi.Â The data were downloaded from the journal's website. The Bibliometric analysis has been conducted with 448 contributions published in the journal selected six years for a period between 2007 and 2012. The analysis covers mainly discuss the each article, year wise distribution of contributions, and number of authorship, volume wise authorship, author's productivity and the single and multi-authored papers and also many more features. Findings of the studies pointed out towards the advantages and weakness of the journal which are helpful for its further development. The result revealed that the highest number of contributions i.e., 87 (19.41 %) were published in the years 2007. The highest number 436 (97.33 %) articles were contributed by joint authors and the rest of 12 (2.67 %) articles contributed by single author. The degree of collaboration is 0.97. The average length of the articles varied from a minimum of 5.94 pages in the year 2012.